Development of a PCR-RFLP marker to genetically distinguish Prosorhynchus crucibulum and Prosorhynchus aculeatus - francisco, cj (2010)
The cercariae stages of Prosorhynchus crucibulum and Prosorhynchus aculeatus are morphologically indistinguishable. However, the differentiation of these two species is crucial to understand the transmission dynamics between these primary hosts (mussels) and the secondary hosts (fish). In this way, the objective of this study is to develop an accurate molecular identification too] to differentiate the cercariae stage of P. crucibulum and P. aculeatus. We targeted the 18S nuclear ribosomal DNA region by PCR amplification and sequenced this amplicon. By generating these sequences, we developed a RFLP tool with the use of the enzymes Hincll and FokI that produced different restriction profiles between P. crucibulum and P. aculeatus. Each enzyme generated different-sized fragments specific to the species examined and no cross-reaction between the species was detected in their restriction pattern. By sequencing, no intraspecific-polymorphism was detected since there is 100% homology among A aculeatus or A crucibulum. These results indicate that PCR-linked restriction analysis of the 18S rDNA region provided us with rapid and reliable molecular tools for distinction of the cercariae of these species. The sequences generated were deposited in GenBank accession numbers for P. crucibulum cercariae (FJ463407, FJ463408 and FJ463409) and adult worm (FJ429096, FJ429097), and for A aculeatus adult (FJ429094 and FJ429095). (C) 2009 Elsevier Ireland Ltd. All rights reserved.